Encyclopedia of Chinese language and linguistics online (Brill, 2015)
The Encyclopedia of Chinese Language and Linguistics offers asystematic and comprehensive overview of the languages of China and thedifferent ways in which they are and have been studied. It providesauthoritative treatment of all important aspects of the languages spoken in China, today and in the past, from many different angles, as well as the different linguistic traditions in which they have beeninvestigated. In more than 500 articles, written by major specialists in the field, the Encyclopedia offers a synthesis of the most importantresearch in Chinese linguistics and up-to-date bibliographical coverage. As such it is the prime reference source for information on: 1) the lexicon, syntax, and sound structure of the Sinitic and non-Sinitic languages of China, including sign languages 2) the history of languages in China and their situation today 3) the history of Chinese linguistics, both indigenous and Western traditions 4) the sociolinguistic situation, language contact, and language variation 5) psycho- and neurolinguistic studies on Chinese, including first language acquisition 6) and many other aspects of Chinese and Chinese linguistics (e.g.,Chinese in the diaspora, Chinese loanwords in other languages, historyof lexicography, language pedagogy, etc.).
Druck-Ausgabe 2015-2017 als fünfbändiges Werk erschienen
Gesehen am 18.05.2020
Keywords: searchable full text; Datenbank; Wörterbuch; Linguistik; Chinesisch